Side Plate Strength Analysis of the Mechanism for Vehicle Axle Scale Calibration - Blatnicky, Miroslav; Dizo, Jan; Blatnicka, Maria (Manufacturing Technology Journal, 2017)
This paper deals with the description of a mechanism for calibration vehicle axle scales with a loading capacity up to 10 tons and strength analysis of its selected part. The strength analysis will be carried out in ADINA software and this analysis results will be used to check the safety of the structure and in case of exceeding the permissible stress, deformation, etc. This analysis results will form a benchmark material for optimisation of this structure. The next step of this issue will be strength analyses of all important parts, i.e. boxes with weights and upper girder. After performing these calculations and the resulting optimisation, the prototype production will be feasible.
Keywords: Test device; Strenght analysis; ADINA software; Vehicle axle scale